EVALUATION OF BLOOD PRESSURE OF SCHOOL OF BASIC EDUCATION OF A PUBLIC SCHOOL OF SANTANA'S IPANEMA, ALAGOAS, BRAZIL (Fiep Bulletin - online, 2013)
The research project aims to expose the problem of hypertension in children making an initial diagnosis and this could contribute and serve as a warning to health professionals and other areas can take action and propose systematic actions to make early diagnosis avoiding future complications consecutive the installation of chronic degenerative diseaseThis project aims at the development of such shares at the Municipal School of Basic Education Santa Sofia, located in the neighborhood of Camoxinga, Rua Santa Sofia, municipality of Santana do Ipanema, Alagoas, Brazil.Want to work with 20% of students from 6th to 9th grade of elementary school afternoon and evening.The aim - to study a sample of 20% of children and adolescents enrolled in the educational institution mentioned above, students of both sexes aged 08-16 years.Initially we intend to conduct an interview, which abordoremos questions about age, weight, manner in which physical activity is doing, if you have any disease, if family members have some disease, proper attire, liquid intake during physical activity and proper nutrition to maintain losing and gaining weight.We start times with dynamic presentation, followed by a round of conversation, where we intend to address various topics, including physical activity and hypertension, the relationship of hypertension with diabetes, the importance of stretching, the use of proper attire and fluid intake and physical activity for improving the quality of life and issues of interest to all, where they will have the opportunity to say what they are feeling.
Keywords: physical activity; health and quality of life